Regulation of Nitrate Reductase in Neurospora crassa: Stability In Vivo - Subramanian, K. N. (1972)
Nicotinamide adenine dinucleotide phosphate, reduced form (NADPH)-nitrate reductase and its related enzyme activities, NADPH-cytochrome c reductase and reduced benzyl viologen-nitrate reductase, are all induced following the transfer of ammonia-grown wild-type Neurospora mycelia to nitrate medium. After nitrate reductase is induced to the maximal level, the addition of an ammonium salt to, or the removal of nitrate from, the cultures results in a rapid inactivation of nitrate reductase and its two partial component activities. This rapid inactivation is slowed down by the protein synthesis inhibitor, cycloheximide. Experiments on the mixing of extracts in vitro rule out the presence of an inhibitor of nitrate reductase in free form in extracts containing inactivated nitrate reductase. Ammonia does not inhibit the uptake of nitrate by the mycelia. Inactivation of nitrate reductase in vivo by ammonia depends on the concentration of the ammonium salt and is not reversed by increasing the nitrate concentration of the medium. The nitrate-inducible NADPH-cytochrome c reductase activity and reduced benzyl viologen-nitrate reductase activity respectively of the nitrate-nonutilizing mutants nit-1 and nit-3 are not inactivated in vivo by the addition of an ammonium salt or the withdrawal of nitrate. This finding suggests that the integrity of the nitrate reductase complex is required for the in vivo inactivation of nitrate reductase and its associated activities.